The expansion of the Prophet’s mosque in Madinah by Caliph al-Walīd (d. 97 AH/ 715 CE) as an epitome of the evolution of Muslim architecture - Omer, Spahic (The Islamic Cultural Centre and London Central Mosque, London, 2017)
This paper discusses the expansion of Prophet Muhammad’s Mosque in Madinah by the Umayyad Caliph al-Walid b. ‘Abd al-Malik. The undertaking is regarded as a microcosm of the evolution of Muslim architecture, which around that time was gaining momentum. The paper concludes that the Mosque expansion project was so multidimensional and two-edged that it personified the major challenges confronting not only the development of Muslim architecture, but also the development of Muslim society at large. Thus, it was apt that ‘Umar b. Abd al-‘Aziz (‘Umar II), one of the most respected and most visionary Muslim rulers, was in charge. The main discussion revolves around three dimensions: tradition versus modernity; the evolution of Muslim architecture between conformity and deviationism; and the relationship between architecture and politics. The three dimensions are discussed after the main aspects of the expansion of the Prophet’s Mosque have been described. Those dimensions, though central to the expansion undertaking, stood likewise at the heart of the evolution of the identity of Muslim architecture. Since architecture is indispensible to life and man’s fulfillment of his purpose on earth, signifying the physical locus, cultural language and identity of society, the dimensions in question, furthermore, stood at the core of the development of Muslim society and its culture and civilization. The paper, it follows, is both Muslim architecture and Muslim society-oriented.